Alternaria keratitis and hypopyon after clear-cornea phacoemulsification - Esposito, Evangelina (2014)
We report a case of Alternaria keratitis and hypopyon following clear-corneal cataract surgery. A 66-year-old woman presented with a painful red left eye several months after uneventful self-sealing clear-corneal phacoemulsification that was unresponsive to prolonged treatment with topical/oral quinolones and topical corticosteroids. A full-thickness stromal white dense infiltrate in the area of the intrastromal tunnel incision and a 2.0 mm hypopyon were observed. Culture from corneal scrapings revealed Alternaria species. Treatment included topical and subconjunctival injections of amphotericin-B (5 mg/mL) and 200 mg of oral ketoconazole. Complete resolution of the corneal infiltration and hypopyon was observed after 30 days of treatment, with no recurrence during 6 years of follow-up. To our knowledge, this is the first report of Alternaria species keratitis complicating self-sealing clear-corneal cataract surgery. Topical and subconjunctival injections of amphotericin-B and oral ketoconazole were effective in resolving the corneal abscess and anterior chamber inflammatory reaction. Financial Disclosure No author has a financial or proprietary interest in any material or method mentioned.